2014
DOI: 10.1111/srt.12183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of washing of the face with a mild facial cleanser formulated with sodium laureth carboxylate and alkyl carboxylates on acne in Japanese adult males

Abstract: Washing the face twice a day with facial cleanser based on AEC/soap is an effective care for moderate or less grade facial acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 21 publications
2
21
0
1
Order By: Relevance
“…We demonstrated that following use of the AEC/AC cleanser, acne lesions were significantly improved. This is similar to a study conducted on male Japanese subjects . It is presumed that this improvement might be caused by the higher sebum‐cleansing ability of these cleansers compared with soap, as shown in Figure .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We demonstrated that following use of the AEC/AC cleanser, acne lesions were significantly improved. This is similar to a study conducted on male Japanese subjects . It is presumed that this improvement might be caused by the higher sebum‐cleansing ability of these cleansers compared with soap, as shown in Figure .…”
Section: Discussionsupporting
confidence: 88%
“…The AEC/AC‐formulated cleanser did not induce dry skin . In the present trial, there were no complaints about facial dryness, and in fact, 4 of the 17 subjects reported that their skin became less dry.…”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations